Clinical factors associated with subsequent surgical intervention in women undergoing early medical termination of viable or non-viable pregnancies - Au, Heng-Kien; Liu, Chi-Feng; Chien, Li-Wei (Frontiers in Medicine, 2024)
Introduction Mifepristone-misoprostol treatment for medical abortion and miscarriage are safe and effective. This study aimed to assess clinical factors associated with subsequent surgical intervention after medical termination of early viable or non-viable pregnancy. Methods This retrospective, single-center study included women who underwent medical abortion at Taipei Medical University between January 2010 and December 2019. A total of 1,561 subjects, with 1,080 viable and 481 non-viable pregnancies, who were treated with oral mifepristone 600 mg followed by misoprostol 600 mg 48 h later were included. Data of all pregnancies and medical termination of pregnancy were evaluated using regression analysis. The main outcome was successful termination of pregnancy. Results The success rate of medical abortion was comparable in women with viable and non-viable (92.13% vs. 92.93%) pregnancies. Besides retained tissue, more existing pregnancies with ultrasonographic findings were found in the non-viable pregnancy group than in the viable pregnancy group (29.4% vs. 14.1%, p = 0.011). Multivariate analysis showed that previous delivery was an independent risk factor for failed medical abortion among all included cases. In women with viable pregnancy, longer gestational age [adjusted odds ratio (aOR): 1.483, 95% confidence interval (CI): 1.224–1.797, p < 0.001] and previous Cesarean delivery (aOR: 2.177, 95% CI: 1.167–40.62, p = 0.014) were independent risk factors for failed medical abortion. Number of Cesarean deliveries (aOR: 1.448, 95% CI: 1.029–2.039, p = 0.034) was an independent risk factor for failed medication abortion in women with non-viable pregnancies. Conclusion This is the first cohort study to identify risk factors for subsequent surgical intervention in women with viable or non-viable pregnancies who had undergone early medically induced abortions. The success rate of medical abortion is comparable in women with viable and non-viable pregnancies. Previous delivery is an independent risk factor for failed medical abortion. Clinical follow-up may be necessary for women who are at risk of subsequent surgical intervention.